Upaya Penyelesaian Pembiayaan Murabahah yang Bermasalah di KSPPS BMT Mitra Umat Pekalongan Cabang Krapyak Tahun 2021 - Nurma Nabila; Akhmad Jalaluddin; Bunga Desyana Pratami (el hisbah: Journal of Islamic Economic Law, 2022)
Non-performing financing is something that is not expected by any financial institution that provides financing products because it can have a bad impact, namely losses due to a decrease in the income of the financial institution. So we need an appropriate effort to resolve the problematic financing. The formulation of the problem in this study is what are the supporting and inhibiting factors for efforts to resolve problematic murabahah financing at KSPPS BMT Mitra Umat Pekalongan Krapyak Branch in 2021 and how is the suitability of efforts to resolve problematic murabahah financing at KSPPS BMT Mitra Umat Pekalongan Krapyak Branch in 2021 with the DSN Fatwa- MUI and KHES. The type of research is sociological juridical and bottom-up research approach with data collection techniques carried out through interviews with BMT, financing supervision and several customers with financing problems and documentation. In this study used analytical descriptive analysis techniques. The results of the study indicate that the factors that support efforts to resolve problematic murabaha financing are supervision and communication to customers; customer awareness and good faith; cooperative customer to the agreement; and the existence of a team of lawyers who provide a deterrent effect. While the inhibiting factor is the character of the customer; customer dishonesty; unstable economic conditions; and customers are reluctant to sell collateral. There are several points that are not in accordance with the provisions of the DSN-MUI and KHES fatwas, namely the points regarding debt relief at the guarantee execution stage, contract conversion points. KSPPS BMT Mitra Ummah Pekalongan Krapyak Branch does not apply any sanctions to customers who delay payments, but charges compensation for transportation costs when billing to customers' homes.